Elephant movement in W Regional Park, western Africa - Audrey Ipavec; Daniel Maillard; Philippe Chardonnet; Camille Danes; Mamoudou Wally; Moussa Lompo; Dominique Dulieu (Pachyderm)
Few studies have focused on the elephant population of W Regional Park in western Africa (Benin, Burkina Faso and Niger) with an essentially national perspective rather than a transfrontier one. During a four-month period from April to July 2004, two elephant females were radio-tracked to establish their transfrontier movements. A total of 556 locations were recorded. Home range sizes calculated using the 95% Kernel method were estimated at 2572 km 2 for one female and 1970 km 2 for the other. Home ranges for the two females largely overlapped with close associations recorded during the tracking period. Movements from Niger to the central part of the park (Burkina Faso) through northern Benin were observed at the beginning of the rainy season along the Mekrou River. Regional survey and management practices should be encouraged to allow this remaining large elephant population to maintain itself.